Optimization of Essential Oil Extraction of Beluntas (Pluchea Indica L.) Leaves by Using Solvent-Free Microwave Extraction - Nur Karima; Nova Chintya Kurniawati; Boy Arief Fachri; Istiqomah Rahmawati; Bekti Palupi; Mahfud Mahfud; Ditta Kharisma Yolanda Putri; Atiqa Rahmawati; Badril Azhar; Maktum Muharja (Jurnal Teknik Kimia dan Lingkungan, 2022)
Beluntas (Pluchea Indica L.) which commonly used as astringent and antipyretic has a high potential for the feedstock of essential oil production. The objective of this work is to optimize solvent-free microwave extraction (SFME) of Beluntas leaves by using response surface methodology (RSM). Box-Behnken Design with the variations of extraction time (60-120 min), feed/distiller ratio (0.06-0.1 g/ml), and heating power (150-450 W) was utilized to optimize essential oil yield. The feed/distiller ratio factor had the highest significant effect on the essential oil yield (P<0.05). Essential oil yield increased as the increase of oil heating power and time extraction, and vice versa. On the other hand, the increase in the feed/distiller ratio gave a negative impact on the essential oil yield. The maximum essential oil yield using SFME method of 0.2728 b/b% was obtained for the optimized condition of extraction time of 90 min, microwave heating power of 450 W, and feed/distiller ratio of 0.06.